Dental Malpractice in Prosthodontics, Endodontics, and Restorative Dentistry: The Prevalence in Saudi Arabia - Rahaf Safadi, Reef Al-Safadi , Riham Al-Safadi , Aisha Qureshey , Eiman Qureshey , Médina Kerdjani , Noor Al-Swaje , Hind Al-Otaibi (International Journal of Emerging Trends in Science and Technology, 2018)
Aim: The aim of this study was to detect the prevalence of dental malpractice in the fields of prosthodontics, endodontics, and restorative dentistry in the Kingdom of Saudi Arabia. Materials and Methods: 251 patients ≥18 years of age selected randomly were examined clinically for substandard dental treatments done in dental premises in KSA in the following fields: Prosthodontics (substandard crown and bridge placement in relation to tooth preparation and crown adaptation, PFM crown and bridge placement on feather edge finishing line, substandard post and core), endodontics (substandard root canal (RCT) treatment), and restorative dentistry (overhanging restorations: class II, III, IV, V). The data obtained were documented in a patient examination form then statistically analyzed using Chi-Square Test. Results: There was a significant difference in the percentages (number) of dental malpractice observations in all of the three types (prosthodontics, endodontics, restorative dentistry) p-value =0.001<0.05, and the dental malpractice observations were not equally distributed. Therefore, endodontics malpractice was of the first rank up to 40% followed by restorative dentistry malpractice of the second rank up to 33% then prosthodontics malpractice of the third rank up to 27%. Conclusion: Dentists must consider ethical principles and acceptable standards and protocols of diagnosis and treatment. There is high need for improving the technical skills of practitioners in root canal treatments. Also, stressing on the importance of using wedges to avoid overhanging dental restorations. Social and economic factors in the Saudi society might play a role in the lower percentages of prosthodontics malpractice in KSA. Keywords: Malpractice, Prosthodontics, Endodontics, Restorative Dentistry.